Influence of ambient gas on the growth and properties of porous tin-doped indium oxide thin films made by pulsed laser deposition - Savu, R.; Joanni, E. (Elsevier B.V., 2007)
The laser ablation method was used for depositing porous nanocrystalline indium-tin oxide thin films for gas sensing applications. Samples were prepared at different pressures using three gases (O-2, 0.8N(2):0.2O(2), N-2) and heat-treated in the same atmosphere used for the ablation process. X-ray diffraction results show that the films are not oriented and the grain sizes are in the range between 15 and 40 nm. The grains are round shaped for all samples and the porosity of the films increases with the deposition pressure. The degree of sintering after heat treatment increases for lower oxygen concentrations, generating fractures on the surface of the samples. Film thicknesses are in the range of I pm for all gases as determined from scanning electron microscopy cross-sections. Electrical resistance varies between 36.3 ohm for the film made at 10 Pa pressure in N-2 until 9.35 x 10(7) ohm for the film made at 100 Pa in O-2. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: laser ablation; ITO; thin films; porosity; resistance